Community Building in the Digital Age: Fostering Brand Loyalty - Asakdiyah, Salamatun; Perdana Oskar, Dimas (Escalate : Economics and Business Journal, 2024)
This study examines the interplay of brand loyalty, community building, digital engagement, and consumer engagement within PT. ISAM (Industri Susu Alam Murni), a dairy company. Using a quantitative research approach and Structural Equation Modeling (SEM) with Smart PLS as the analytical tool, data from 100 consumers were analyzed to assess direct and indirect effects among these variables. The findings reveal that while community building efforts showed no significant direct impact on brand loyalty, digital engagement significantly influences consumer engagement, which in turn positively affects brand loyalty. These results underscore the critical role of effective digital strategies in fostering consumer participation and advocacy, thereby enhancing brand loyalty in the competitive dairy industry landscape. The study contributes insights that can guide strategic decision-making and marketing efforts aimed at cultivating stronger brand-consumer relationships and improving market positioning for PT. ISAM and similar companies in the dairy sector.